Early treatment response of a rare papillary tumor of the pineal region after primary proton-beam therapy using the raster-scanning technique at HIT - Habermehl, Daniel; Blachutzik, Florian; Ecker, Swantje; Dittmar, Jan Oliver; Rieken, Stefan; Debus, Jürgen; Welzel, Thomas; Combs, Stephanie (Tumori journal, 2012)
Pineocytomas are rare intracranial tumors occurring in the pineal gland region. The curative therapy of choice is gross total resection, which cannot be performed in all patients because of the frequent eloquent location of these tumors. Percutaneous fractionated radiotherapy is an alternative treatment approach that may result in high local control rates. Nevertheless, our knowledge of this tumor entity is limited and based on retrospective case series only. We present a patient with a papillary tumor of the pineal region who was treated with highly conformal proton-beam therapy at the Heidelberg Ion Therapy Center (HIT) using the raster-scanning technique.
DOI funktioniert nicht
Gesehen am 16.10.2018